The effectiveness of market service fee collection management at Nanggalo Market in increasing local revenue (PAD) for Padang City - Iis Mardiana Firjayanti; Syamsir Syamsir (Priviet Social Sciences Journal, 2025)
The aims of this study were to determine the effectiveness of market service fee collection management at Nanggalo Market in increasing the local revenue of Padang City, to identify obstacles, and to develop plans to improve performance All 12 traders, the head of the Nanggalo Market Technical Implementation Unit, fee collectors, and employees of the Padang City Trade Office were used as informants. Interviews, field observations, and document studies were used to collect the data. The data validity was tested using triangulation techniques and data sources. The data analysis used the interactive model of Miles, Huberman, and Saldana, which included data presentation, conclusion drawing, and data reduction. Although the target was achieved, the QRIS e-retribution system had a high level of merchant compliance. There are issues with centralistic planning, labor shortages, inadequate telecommunications infrastructure, lack of transparency, and lack of digital literacy. Therefore, even though the target was achieved, the retribution management of the Nanggalo Market is still not optimal overall. Therefore, a participatory forum and the improvement of officers are needed.